Analysis of Environmental Sanitation Factors and Personal Hygiene on the Incidence of Tuberculosis in Jember Regency - Firjoun Ali Muhammad; Al Munawir; Isa Ma’rufi (Poltekkes Kemenkes Surabaya, 2024)
Many risk factors can trigger tuberculosis, including environmental sanitation and personal hygiene. Personal hygiene is crucial because it involves actions taken by an individual to maintain their physical and psychological cleanliness and health. Meanwhile, environmental sanitation factors include the availability of clean water (whether clean water meets physical water quality standards is available) and solid waste management (mechanisms for providing trash bins and waste disposal). This study aims to analyze the relationship between environmental sanitation and personal hygiene on the incidence of tuberculosis in Jember Regency. This research method uses observational analytics with a case-control study design. The study sample consisted of 52 individuals in the control group and 52 in the case group. The sampling technique used was Cluster Random Sampling. The statistical tests used were bivariate (chi-square test) and multivariate (multiple linear regression). The findings revealed a significant relationship between environmental sanitation (p=0.004) and no significant relationship with personal hygiene (p=0.282). The results concluded that among all the independent variables suspected to influence the incidence of tuberculosis, environmental sanitation was the most influential factor.